ANATOMO-MORPHOMETRIC PARTICULARITIES OF THE INTERNAL JUGULAR VEIN. A REVIEW - Tatiana Cotoneț; Zinovia Zorina (Arta Medica, 2021)
Objectives. The aim of the study was to analyze data and evidence from existing literature sources, regarding the topographic and morphometric features of the internal jugular vein, according to gender, age, laterality and its role in contemporary medicine.